Dehydration-induced folding of poly(ε-caprolactone)-agarose hydrogel composites. (August 2019) - Aaron, Foster; Clare, Moore; Bastian, Brockhoff; Fredrick, Khayad; Tim, Dargaville; Aurelien, Forget
Graphical abstract: Abstract: Materials that can be actuated by external stimuli are of particular interest for the manufacturing of interactive objects. Such materials open the possibility to change the shape of objects in response to external conditions, such as humidity. Biocompatible and biodegradable materials like agarose and poly(ε-caprolactone) (PCL) are of high interest as they can lead to objects able to interact with biological systems for instance for the implantation of small print-size object that could deploy under physiological conditions. However, these are not typical candidate materials for the manufacturing of interactive objects. In this study, a composite material was made by reinforcing agarose hydrogels with PCL scaffolds, and upon dehydration a predictable folding of the composites was obtained. More interestingly, this folding is shown to be reversible upon rehydration. Starting with a simple rectangular shape, we designed foldable structures with 1, 3 and 4 hinges. Subsequently, a triangular shape that automatically folds into a pyramid was manufactured. The actuation time, actuation intensity and mechanical properties were measured and correlated with scaffold design.